Kampanye Sosial Pemanfaatan Pakaian Lama Dengan Metode Upcycle Kepada Generasi Z Di Kota Palembang - Pratama, Aditya; Iswandi, Heri; Dion, Keni (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
The impact of textile waste is a serious problem for health and the environment. Generation Z often chooses to throw away clothes rather than looking for ways to reuse them and not many are aware that these used items can be recycled into items that have benefits and economic value. Generation Z's lack of awareness of the dangers of textile waste and lack of education about upcycling methods are the main problems in this design. Therefore, it is necessary to design a campaign video that can widely reach Generation Z with the aim of making it easier to provide information about upcycling methods and providing awareness of the dangers of textile waste. The main aim of the design is to provide information about how important it is to use used clothing waste in the city of Palembang, to raise awareness and encourage that used clothing waste can be put to good use. Apart from being useful for protecting the environment, used clothing waste can also produce positive feedback from its use.Keywords : Textile waste, Upcycling, Clothing, Campaign Videos.